2013
DOI: 10.1042/bj20130556
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-2 is essential for c-Jun transcriptional activation and Bim induction in neuron death

Abstract: SYNOPSIS Neuronal apoptotic death generally requires de novo transcription, and activation of the transcription factor c-Jun has been shown to be necessary in multiple neuronal death paradigms. Caspase-2 has been implicated in death of neuronal and non-neuronal cells, but its relationship to transcriptional activation has not been clearly elucidated. Here, using two different neuronal apoptotic paradigms, β-amyloid treatment and NGF withdrawal, we examined the hierarchical role of caspase-2 activation in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…In accord with in vitro studies, we and others have shown that Aβ 1-42 directly infused into the hippocampus elicits neuron death 1,4,9,10 , depicting one of the key features of AD. The degeneration is clearly evident in the vicinity of the injection site as shown by a decreased in the volume of the dentate gyrus that is complemented by increases in markers for degeneration 1 .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In accord with in vitro studies, we and others have shown that Aβ 1-42 directly infused into the hippocampus elicits neuron death 1,4,9,10 , depicting one of the key features of AD. The degeneration is clearly evident in the vicinity of the injection site as shown by a decreased in the volume of the dentate gyrus that is complemented by increases in markers for degeneration 1 .…”
Section: Discussionmentioning
confidence: 84%
“…These low molecular weight Aβ 1-42 species, but not the fibrils and plaques, have been shown in numerous settings to be most toxic to neurons 1,4,9,[17][18][19] . To determine whether or not oligomeric Aβ 1-42 induces neuron death in the mouse brain Aβ 1-42 (4 µl of 100 µM stock solution) was infused into the DG of the hippocampus in one hemisphere of 9 month old wild-type C57BL/6J mice.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we and many others have demonstrated that rodent neurons exposed to amyloid peptides are susceptible of Aβ-induced toxicity and other phenotypes, including tau phosphorylation and synaptic alterations (8)(9)(10)(11)(12).…”
Section: Subhead 4: Empirical Evidence For Jak-stat Dysregulation In mentioning
confidence: 99%